An automatic measure of progression during colonoscopy correlates to patient experienced pain. (4th March 2018) - Preisler, Louise; Bulut, Mustafa; Svendsen, Morten Soendergaard; Svendsen, Lars Bo; Konge, Lars
Abstract: Background: Colonoscopy screening and surveillance programs depend on patient's tolerable experience, which is associated with competence of the endoscopist. The Colonoscopy Progression Score (CoPS) is an automated tool based on recording of the Magnetic Scope Imager (MEI) picture in order to track progression. CoPS deliver a numeric score and a graphic map. A high score expresses a rapid and smooth progression. Aims of study were to explore the correlation between CoPS and patient experienced pain and to identity locations associated with pain. Methods and materials: Patients listed for colonoscopy were included and asked to reply to pain by pressing a rubber ball. The signal was recorded simultaneous to CoPS. Patients evaluated the experience on a Visual Analogue Scale (VAS). CoPS and recorded pain events were used to create a pain sensitive CoPS-map (S-CoPS map). Results: A total of 58 complete recordings were used for evaluation. We demonstrated a moderate correlation between CoPS and patient experienced pain, Pearson's r = −0.47 ( p < .001). A low CoPS was associated with a painful colonoscopy and a high CoPS excluded severe pain. Sensitivity and specificity was 0.79 and 0.60 and AUC was 0.61 Passage of the sigmoid colon, right and left flexures were associated with pain for 51%, 33% and 25% of the patients, respectively. Conclusion: A moderate correlation between CoPS and patient experienced pain suggest that CoPS measure inserting skills but might also be a measure of a gentle performance. The graphic S-CoPS-map can be used to point-out painful passages and aid planning of future colonoscopies.